Reliability and Validity of the Fagerstrom Test for Cigarettes Dependence among Malaysian Adolescents - Kuang Hock LIM; Chien Huey THE; Hui Li LIM; Yi Yi KHOO; Keng Joo LAU; Chan YY; Sumarni MOHD GHAZALIG; Chee Cheong KEE CC; Kuang Kuay LIM; Normala IBRAHIM; Fadhli Mohd YUSOFF (Tehran University of Medical Sciences, 2016)
No Abstract.